If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 6) + -6x = -2(1 + 5x) Reorder the terms: -3(6 + x) + -6x = -2(1 + 5x) (6 * -3 + x * -3) + -6x = -2(1 + 5x) (-18 + -3x) + -6x = -2(1 + 5x) Combine like terms: -3x + -6x = -9x -18 + -9x = -2(1 + 5x) -18 + -9x = (1 * -2 + 5x * -2) -18 + -9x = (-2 + -10x) Solving -18 + -9x = -2 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -18 + -9x + 10x = -2 + -10x + 10x Combine like terms: -9x + 10x = 1x -18 + 1x = -2 + -10x + 10x Combine like terms: -10x + 10x = 0 -18 + 1x = -2 + 0 -18 + 1x = -2 Add '18' to each side of the equation. -18 + 18 + 1x = -2 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = -2 + 18 1x = -2 + 18 Combine like terms: -2 + 18 = 16 1x = 16 Divide each side by '1'. x = 16 Simplifying x = 16
| 7=2+5(z-2) | | 2x+8x=2(x+1)+5(8x+6) | | 12x+23=5x+205 | | 4(2+n)=-2(n+4)+4 | | 161-4x=23x+23 | | 4(2+n)=-2(n+4 )+4 | | 7-8x=22-15x | | 4(2+n)=-2(1+5n) | | -155-8x=9x+15 | | 2+10x=92+x | | 4(2+n)=-2(1+5x) | | 2x+11=-9-8x | | x+[x(.08)+x(.20)]=1280 | | 0=x^2-4x-7 | | -25-5x=7-9x | | 3c^2-8c+5=0 | | -2x-2=11 | | 8(a-7)=6(1+8a)+6a | | 5x-2=13x-98 | | -2(1-3r)+5=3(4+3r) | | 4.85=0.05(p)+1.85 | | 3x+34=12x-74 | | -7(2-2a)=-2(-4a+7) | | y=0.05(28)+1.85 | | 6(p+8)=-4(2p-5) | | 81b^2-100=0 | | -[6x-(4x+8)]=9+(6x+3) | | -(p+2)=2(p-7) | | 88-42=2.66(h-7) | | p-42=2.66(20-7) | | x+4=28 | | p-42=2.66(18-7) |